(3QSGdI GdWjQs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3bGd GdTjN GHf SjfG Gddge GdGNhGf LeYJge GdbQGHI GdCdgjI hCdaJ Hjfge GdeLGhQI GdYdhjI s
(3BNQgG (B:s
(3hHGddg GdGSJYGfI hef GdfGS GdHQGI hef GYJbO ZjQ gPG NSQ hSjYde GdXGdehf Edi eGPG jfbdHhf s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdYGTQIs
(3HgG fXGe GdJYbjHIs
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3CNdGb JjehQ (B290) s
Keywords: (3GdadSaI hGdefWbs